2005
DOI: 10.1021/om058044+
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Reactivity of Heteropentadienyl−Transition-Metal Complexes

Abstract: The synthesis and reactivity of transition-metal complexes containing heteropentadienyl ligands (i.e., pentadienyl analogues in which one terminal carbon has been replaced by a heteroatom) are reviewed. Specifically, four compound classes are covered:  oxapentadienyl−metal, azapentadienyl−metal, thiapentadienyl−metal, and phosphapentadienyl−metal complexes. Within each of these classes, contributions are presented in approximate chronological order. Particular attention is given to the development of rational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 66 publications
1
16
0
Order By: Relevance
“…Synthesis and spectroscopy of [(1,2,3-h 3 )-(5-tert-butylazapentadienyl)] 2 Ru(PPh 3 ) 2 (1) Treatment of Cl 2 Ru(PPh 3 ) 3 [5] with two equivalents of potassium tert-butylazapentadienide [6] leads to the production of [(1,2,3-h 3 )-(5-tert-butylazapentadienyl)] 2 Ru(PPh 3 ) 2 (1) as a yellowbrown microcrystalline powder (see Scheme 1). The same product (albeit in reduced yield) is observed even when less than two equivalents of potassium tert-butylazapentadienide are used; there is no evidence of a mono-azapentadienyl-ruthenium product.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthesis and spectroscopy of [(1,2,3-h 3 )-(5-tert-butylazapentadienyl)] 2 Ru(PPh 3 ) 2 (1) Treatment of Cl 2 Ru(PPh 3 ) 3 [5] with two equivalents of potassium tert-butylazapentadienide [6] leads to the production of [(1,2,3-h 3 )-(5-tert-butylazapentadienyl)] 2 Ru(PPh 3 ) 2 (1) as a yellowbrown microcrystalline powder (see Scheme 1). The same product (albeit in reduced yield) is observed even when less than two equivalents of potassium tert-butylazapentadienide are used; there is no evidence of a mono-azapentadienyl-ruthenium product.…”
Section: Resultsmentioning
confidence: 99%
“…Heteropentadienyl ligands (i.e., pentadienyl analogues in which one carbon has been replaced by a heteroatom such as O, S or NR) have attracted increasing attention because of their ability to access a wide variety of bonding modes in transition metal complexes [2,3]. Interconversions between these modes can enhance stoichiometric reactivity and perhaps even be used to open and close coordination sites in catalytic cycles.…”
Section: Introductionmentioning
confidence: 99%
“…The electrolysis of compounds 1, 2 and 3, in MeCN and 0.2 M n-Bu 4 NPF 6 , afforded the thermodynamic product 4 and the corresponding kinetic products 5, 6 and 7, which could not be isolated from the electrolysis mixtures. Compound 4 was synthesized independently from (Cp * RuCl) 4 and AgPF 6 in acetonitrile following the procedure previously reported [12] in order to confirm the corresponding assignments of the electrolysis mixture.…”
Section: Instrumentationmentioning
confidence: 99%
“…A key feature of acyclic pentadienyl and heteropentadienyl ligands, such as the oxopentadienyl, is their ability to adopt a variety of bonding modes and to shift easily among them [1][2][3][4][5]. This surprising versatility leads to enhance reactivity at the metal center and raises the possibility of using ligand shifts (g 5 ¢ g 3 ¢ g 1 ) to open and close coordination sites and change the oxidation states.…”
Section: Introductionmentioning
confidence: 99%
“…The group 14 metal (M) 1-azapentadienyls were prepared from the W-shaped Li[N(Bu t )(CH) 3 CH 2 ] and M(Cl)Me 3 ; for M = Si, the E,E-compound D was the sole product, but both D and the E,Z-D 0 were isolated for M = Sn [6]. Bleeke's review of heteropentadienyl-transition metal complexes included a section on azapentadienyls [9]. Paz-Sandoval and Rangel-Salas surveyed group 1 metal, Mg, group 14-and d-metal azapentadienyls; such lithium, trimethylsilyl and stannyl compounds are of ''increasing importance in organic synthesis, either as reagents for selective transformations or as intermediates for the creation of carbon-carbon bonds" [10]; they also suggested that the structure of A was better represented by A 0 .…”
Section: Introductionmentioning
confidence: 99%